2023
DOI: 10.3389/fphar.2022.1080753
|View full text |Cite
|
Sign up to set email alerts
|

Miracle fruit seed as a potential supplement for the treatment of learning and memory disorders in Alzheimer’s disease

Abstract: Currently, the treatment of Alzheimer’s disease (AD) is still at the stage of symptomatic treatment due to lack of effective drugs. The research on miracle fruit seeds (MFSs) has focused on lipid-lowering and antidiabetic effects, but no therapeutic effects have been reported in AD. The purpose of this study was to provide data resources and a potential drug for treatment of AD. An AD mouse model was established and treated with MFSs for 1 month. The Morris water maze test was used to assess learning memory fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…The molecular docking predictions showed that the seed compounds were stably bound to core targets, specifically AKT1, EGFR, ESR1, PPARA, and PPARG. Thus, the seeds are discussed to potentially play a therapeutic role in AD by affecting the insulin signaling pathway and the Wnt pathway [36]. Ginkgo biloba L. leaves have shown potentially beneficial effects for people with dementia, when it is administered at doses greater than 200mg/day for at least 5 months [37].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking predictions showed that the seed compounds were stably bound to core targets, specifically AKT1, EGFR, ESR1, PPARA, and PPARG. Thus, the seeds are discussed to potentially play a therapeutic role in AD by affecting the insulin signaling pathway and the Wnt pathway [36]. Ginkgo biloba L. leaves have shown potentially beneficial effects for people with dementia, when it is administered at doses greater than 200mg/day for at least 5 months [37].…”
Section: Discussionmentioning
confidence: 99%
“…This enables the PI 3 K/Akt signaling pathway to operate normally, avoiding neuroin ammation, oxidative stress, and other pathological processes. 75 STAT3 encodes a protein that belongs to the STAT family of proteins. It plays a crucial role in various cellular processes such as cell growth and apoptosis.…”
Section: Discussionmentioning
confidence: 99%